2015
DOI: 10.1111/aab.12188
|View full text |Cite
|
Sign up to set email alerts
|

A cixiid survey for natural potential vectors of ‘Candidatus Phytoplasma phoenicium’ in Lebanon and preliminary transmission trials

Abstract: Almond witches'-broom (AlmWB) disease, associated with 'Candidatus Phytoplasma phoenicium', is an emerging threat with real risk of introduction in Euro-Mediterranean Countries. Its rapid spread over large geographical areas suggests the presence of efficient insect vector(s). In the present work, a survey on cixiids was carried out in Lebanon in the years 2010-2013 in AlmWB-infested almond and nectarine orchards. Insects were collected by means of different methods, identified with a stereo microscope, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…P. phoenicium’ strains infecting almond, peach and nectarine in Lebanon (i) revealed a substantial genetic homogeneity within the analyzed phytoplasma populations based on house-keeping gene sequence analyses, and (ii) allowed the identification of distinct AlmWB-associated phytoplasma strains from diverse host plants based on inmp (integral membrane protein) gene sequence analysis. This evidence, along with prior reports of multiple insect vectors of AlmWB phytoplasma [ 56 , 57 ], suggests that AlmWB could be associated with phytoplasma strains derived from the adaptation of an original strain to diverse hosts.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…P. phoenicium’ strains infecting almond, peach and nectarine in Lebanon (i) revealed a substantial genetic homogeneity within the analyzed phytoplasma populations based on house-keeping gene sequence analyses, and (ii) allowed the identification of distinct AlmWB-associated phytoplasma strains from diverse host plants based on inmp (integral membrane protein) gene sequence analysis. This evidence, along with prior reports of multiple insect vectors of AlmWB phytoplasma [ 56 , 57 ], suggests that AlmWB could be associated with phytoplasma strains derived from the adaptation of an original strain to diverse hosts.…”
Section: Discussionsupporting
confidence: 61%
“…Intriguingly, these preliminary data seem to indicate that AlmWB phytoplasma strains identified in peach plants are distinct from strains infecting almond and nectarine based on molecular markers within the inmp nucleotide sequences. Recently, insect species of the families Cicadellidae and Cixiidae have been reported to be capable of transmitting AlmWB phytoplasma [ 56 , 57 ]. Considering this evidence, it is reasonable to hypothesize the possible implication of inmp diversity on multiple vector-specific epidemiological cycles of AlmWB phytoplasma in the diverse plant hosts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this leafhopper has been reported from almond orchards in Iran [ 89 ]. Transmission trials by Tachycixius viperinus Dlabola and T. cypricus Dlabola revealed that they can transmit the 16SrIX-B phytoplasma to peach in Lebanon [ 90 ]. T. viperinus and T. cypricus , collected from Anthemis spp.…”
Section: Phytoplasmas Associated With Fruit Cropsmentioning
confidence: 99%
“…T. viperinus and T. cypricus , collected from Anthemis spp. and Smilax aspera , which were grown in the wild in Lebanon, also tested positive to AlmWB phytoplasma strains [ 90 ]. However, the vector of AlmWB disease has not been identified in Iran [ 73 , 80 ].…”
Section: Phytoplasmas Associated With Fruit Cropsmentioning
confidence: 99%
“…with witches' broom in the USA (Davis et al, 2010). Phytoplasmas are mostly transmitted by leafhoppers which can feed on different plant host species and can also be transmitted from reservoir hosts to cultivated or forest and shrub plants (Abou-Jawdah et al, 2014;Casati et al, 2016;Tedeschi et al, 2014). Little is known about the economic importance of phytoplasma infection in forest and shrub plants, including D. mucronata.…”
Section: Re Sultsmentioning
confidence: 99%